Primary malignant melanoma of prostate - Doublali, M. (Medknow Publications, 2010)
Primary genitourinary melanoma accounts for less than one per cent of all cases of melanoma. Most cases attributed to the prostate actually originate from the prostatic urethra. Due to its infrequency, primary malignant melanoma of the genitourinary tract presents a difficult diagnostic and management challenge. We report a case of primary malignant melanoma of the prostate found during transurethral resection of the prostate.